Sobre a complexidade envolvida no diagnóstico precoce de autismo: uma questão de linguagem - Prisco, Ana Carolina (2019)
The questions that guide this project come from a care of a child of one year and six months realized in a Center of Specialized Attention (CER) agreed to SUS. This child presented an embarrassment in the relationship with language and in relation to the other. The proposition of a language service for such a child took into consideration the solidarity between the acquisition of language and the subjective constitution (DE LEMOS, 2002). It is known that the number of cases diagnosed as Autism Spectrum Disorder (ASD) has multiplied by ten in the last twenty years (LAURENT, 2014). At the same time, attention to mental health in early childhood has become a topic that gains space and relevance since the publication of the Legal Framework for Early Childhood (Law 13.257 / 2016), which provides for the need for follow-up and promotion of child development and the approval of Law 13388/17, which establishes the mandatory application of a tool to detect risk for psychic development during the first 18 months of life. In this research, I aim to: (1) address issues of a theoretical nature, based on a narrative bibliographic review and critical review of the work on autism, and "psychic risk", focusing on the way language is approached; (2) to present a case related to a patient who arrives early in the speech-language clinic. The theoretical foundations that support this research give recognition to the achievements made in the Language Clinic (Lier-DeVitto, 2006 and others), based on a relation of alterity with the Interactionism in Acquisition of language (as proposed by De Lemos (from 1982) and that has European structuralism (Saussure, Jakobson and Benveniste) as the soil for language thinking, as well as sustaining the notion of the unconscious introduced by Freud (1900). The literature on early diagnosis of ASD is heterogeneous, part of which understands that children with early signs of the disease should be evaluated and diagnosed. Works from another theoretical current understand that the first signs detected in the child should be accepted, and the diagnosis be suspended, understanding that the child’s condition may have a destination other than the ASD. The language in such works, when it is not left out of the discussion, remains strongly tied to communicative development. In the narrative of the Joana case, I sought to situate a clinic in which the signs are taken as one child's position facing the other and facing language, including the structural reasoning in language acquisition proposed by De Lemos (2002), for the understanding of such signs and changes that were observed in the case throughout the care. Changes that were possible in a clinic where the therapist puts himself in a position that holds up a theory of language (LIER-DEVITTO, 2006, ANDRADE, 2006). I understand that, based on the results obtained, it was possible to broaden the discussion about the early diagnosis of ASD and to produce effects for the Collective Health Field, regarding the necessary caution for the reception of children with early signs of ASD and the impossibility of say in advance a pathology